An assessment of irrigation water quality and potential of reusing greywater in home gardens in water-limited environments. (April 2020) - Radingoana, Makgalake P.; Dube, Timothy; Mazvimavi, Dominic
Abstract: In this study, we assess the quality of greywater for reuse in home gardens through irrigation in water-limited environments of the rural Limpopo province, South Africa. To address this objective, pH, Electrical Conductivity (EC), Potassium (K + ), Calcium (Ca 2+ ), Magnesium (Mg 2+ ) and Sodium (Na + ) were tested from the household sampled greywater e.g. kitchens, bath and laundry sampled. Hazards in greywater were determined using water quality indices and the derived results were assessed for any differences using ANOVA and Tukey method. The average pH values of study area 1 (STA1), study area 2 (STA2) and study area 3 (STA3) were found to be slightly alkaline (pH 8–9). Generally, most of the Sodium Adsorption Ratio (SAR) values where within the low category (1–10) indicating its acceptability for reuse. Most water quality parameters had high Soluble Sodium Percentage (SSP), with an average of 68.09%, 79.42% and 92.30% in STA1, STA2 and STA3, respectively. Further, the Kelley's Ratio (KR) indicate elevated levels of salt concentrations in greywater, with exceptions from laundry water in STA1. In contrary, residual chloride levels in all samples were found to be within the acceptable range (0–30meq/L) with <4meq/L having no restrictions. The study, therefore, concludes that untreated water can be used for home gardening irrigation with caution, unless it is diluted with freshwater. Highlights: Crop production is interrupted during the dry season. Greywater can be used to supplement freshwater irrigation during dry seasons. Greywater contains elevated contents of Sodium. Greywater should be used on soil tolerant crops. Continuous greywater irrigation should be avoided.